Kids and sports from infant to athlete - Jennings, Judy; Simmons, Dan; Schrank, Louise Welsh; Learning Seed Company (Illinois : Learning Seed, 2008)
Watch as physical, social and emotional development follow a sequence that adults can't speed up. See just how skills in sports progress from birth through puberty. Marvel at the intellectual side of sports, from score keeping to game strategizing. The program guides viewers through the dangers of the over-scheduled, over-pressured, over-trained child
Title from title screen
Teaching guide for this program available at www.learningseed.com
Executive producer, Joseph Lombardo ; editor, Bill Killian
DVD Format
With English subtitle
Keywords: Sports for children; Child development; Sports for children -- Moral and ethical aspects